9/11 Truth and the Silence of the IR Discipline. Issue 2 (27th February 2020) - Hughes, David A.
International Relations (IR) scholars uncritically accept the official narrative regarding the events of 9/11 and refuse to examine the massive body of evidence generated by the 9/11 truth movement. Nevertheless, as calls for a new inquiry into the events of 9/11 continue to mount, with the International 9/11 Consensus Panel and World Trade Centre Building 7 Evaluation inquiries having recently published their findings, and with a U.S. Federal Grand Jury on 9/11 having been announced, now would be an opportune moment for IR scholars to start taking the claims of 9/11 truth seriously. A survey of the 9/11 truth literature reveals that the official 9/11 narrative cannot be supported at multiple levels. Two planes did not bring down three towers in New York. There is no hard evidence that Muslims were responsible for 9/11 other than in a patsy capacity. Various U.S. government agencies appear to have had foreknowledge of the events and to have covered up evidence. Important questions regarding the hijacked planes need answering, as do questions about the complicity of the mainstream media in 9/11. IR scholars avoid looking at evidence regarding the events of 9/11 for several reasons. They may be taken in by the weaponized term, "conspiracy theory." A taboo on questioning the ruling structures of society means that individuals do not wish to fall outside the spectrum of acceptable opinion. Entertaining the possibility that 9/11 was a false flag requires Westerners to reject fundamental assumptions that they have been socialized to accept since birth. The "War on Terror" has created a neo-McCarthyite environment in which freedom to speak out has been stifled. Yet, if IR scholars are serious about truth, the first place they need to start is 9/11 truth.